2013
DOI: 10.1056/nejmoa1301440
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Patent Foramen Ovale versus Medical Therapy after Cryptogenic Stroke

Abstract: In the primary intention-to-treat analysis, there was no significant benefit associated with closure of a patent foramen ovale in adults who had had a cryptogenic ischemic stroke. However, closure was superior to medical therapy alone in the prespecified per-protocol and as-treated analyses, with a low rate of associated risks. (Funded by St. Jude Medical; RESPECT ClinicalTrials.gov number, NCT00465270.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
621
6
55

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 883 publications
(696 citation statements)
references
References 18 publications
14
621
6
55
Order By: Relevance
“…We identified 9 articles reporting the results of 8 different RCTs meeting the inclusion criteria 7, 8, 9, 10, 11, 12, 30, 31. Four studies (CLOSURE I,7 PC trial,8 RESPECT,10 and DEFENSE‐PFO13) compared PFO closure with antithrombotic therapy (oral anticoagulation or antiplatelet therapy at the discretion of the investigator).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 9 articles reporting the results of 8 different RCTs meeting the inclusion criteria 7, 8, 9, 10, 11, 12, 30, 31. Four studies (CLOSURE I,7 PC trial,8 RESPECT,10 and DEFENSE‐PFO13) compared PFO closure with antithrombotic therapy (oral anticoagulation or antiplatelet therapy at the discretion of the investigator).…”
Section: Resultsmentioning
confidence: 99%
“…Observational studies have demonstrated a strong association between patent foramen ovale (PFO) and cryptogenic stroke,3, 4 suggesting that paradoxical embolism through a PFO may be an important cause of otherwise unexplained ischemic strokes, notably in younger patients 5, 6. Three randomized controlled trials (RCTs) published in 2012 and 2013 (CLOSURE I (STARFlex Septal Closure System in Patients with a Stroke and/or Transient Ischemic Attack due to Presumed Paradoxical Embolism through a Patent Foramen Ovale),7 PC Trial (Clinical Trial Comparing Percutaneous Closure of Patent Foramen Ovale Using the Amplatzer PFO Occluder with Medical Treatment in Patients with Cryptogenic Embolism),8 and RESPECT (Randomized Evaluation of Recurrent Stroke Comparing PFO Closure to Established Current Standard of Care Treatment)9) failed to demonstrate the superiority of PFO closure over antithrombotic therapy (antiplatelet therapy or anticoagulants) to prevent recurrent stroke. Recently, the long‐term analysis of the RESPECT trial10 and 3 other RCTs (Gore REDUCE (Gore Helex septal occluder and antiplatelet medical management for reduction of recurrent stroke or imaging‐confirmed transient ischemic attack in patients with patent foramen ovale),11 CLOSE (Patent Foramen Ovale Closure or Anticoagulants versus Antiplatelet Therapy to Prevent Stroke Recurrence),12 and DEFENSE‐PFO (Device Closure Versus Medical Therapy for Cryptogenic Stroke Patients With High Risk Patent Foramen Ovale)13) reported a lower incidence rate of recurrent stroke in patients randomized to PFO closure compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively high incidence of residual shunts postimplant, embolic event rate remained low and did not correlate with recurrent thromboembolic events 80. A low incidence of significant residual shunts was observed in the recent major trials, 2 of 499 (0.4%) in the RESPECT trial23, 25 and 2 of 238 (0.8%) in the CLOSE trial 27…”
Section: Complications Of Pfo Closurementioning
confidence: 97%
“…One patient had a stroke after randomization before a closure device was placed, the second patient decided not to proceed after the stroke, and the third had a stroke during an unexpected coronary artery bypass graft surgery wherein the PFO was closed surgically. However, in the prespecified per‐protocol cohort, 6 patients in the closure group and 14 in the medical therapy group had a recurrent stroke (HR, 0.37; 95% CI, 0.14–0.96; P =0.03) 23. Although the intention‐to‐treat cohort did not reach significance for the efficacy end point, both the prespecified per‐protocol and as‐treated analyses (5 events in the closure group versus 16 in the medical therapy group) suggested superiority of closure over medical therapy.…”
Section: Pfo Closure For Recurrent Cryptogenic Stroke Preventionmentioning
confidence: 99%
See 1 more Smart Citation